Cost of Illness, Quality of Life, and Work Outcomes in Active Ankylosing Spondylitis Patients Treated With Adalimumab in China - Tu, Liudan; Xie, Ya; Liao, Zetao; Jiang, Yutong; Lv, Qing; Cao, Shuangyan; Wei, Qiujing; Gu, Jieruo (Frontiers in Public Health, 2020)
Objectives: To access the cost of illness, quality of life and work limitation in active ankylosing spondylitis (AS) patients using adalimumab in China. Methods: A prospective study was performed in 91 patients with active AS in China. Adult patients (aged ≥ 18 years) fulfilled the 1984 New York modified criteria of AS with the Bath Ankylosing Spondylitis Disease Activity Index ≥ 4 were enrolled. All participants received adalimumab (40 mg per 2 weeks) therapy and completed questionnaires about disease characteristics, quality of life and cost. Only patients with pay-work completed the Work Limitation Questionnaire and Work productivity and activity impairment questionnaire in AS. Factors associated with work outcomes were evaluated. Results: A total of 91 patients with mean age of 30 years old (87.8% males) and mean disease duration of 10 years received adalimumab treatment for 24 weeks. The annual estimated cost of each patient was $37581.41 while the direct cost accounted for 84.6%. Seventy-eight percent of patients have a paid job with average work productivity loss of 0.28 measured by work limitation questionnaire, absenteeism and presenteeism were 10.22 and 43.86%, respectively, with a mean work productivity loss of 47.92% measured by Work productivity and activity impairment questionnaire in AS. Patients experienced significantly greater improvements after adalimumab treatment in presenteeism, absenteeism, work productivity, and quality of life. Conclusions: The cost of AS patients with adalimumab therapy was high in China. Disease activity, physical function, quality of life, and work outcomes improved significantly after therapy.